Clinical characteristics and literature review of chronic active Epstein–Barr virus‐associated enteritis - Yajie Meng; Rendong Li; JieWen Ding; Bo Xiang; Qin Wang; Min Wang; KeJiang Tang (Clinical Case Reports, 2024)
Key Clinical Message Chronic active Epstein‐Barr virus (EBV) infection‐associated enteritis (CAEAE) in nonimmunodeficient individuals is rare. To report a case of CAEAE, relevant articles were searched through databases. The clinical manifestations, endoscopic findings, strategies of treatment, prognoses, and follow‐up results of CAEAE patients were analyzed. Including this report, seven citations in the literature provide descriptions of 27 cases of CAEAE. There were 21 males and six females, with a mean age of 40 years. The main clinical manifestations were fever (25/27), abdominal pain (14/27), diarrhea (16/27), hematochezia or bloody stools (13/27), and decreased hemoglobin and red blood cell counts in routine blood tests (14/27). Elevations in inflammatory markers, white blood cell (WBC) counts, and C‐reactive protein (CRP) were common. Coagulation was often abnormal. Histopathology confirmed EBV‐encoded small nuclear RNA (EBER) in the affected tissue via in situ hybridization. The average serum EBV DNA load was 6.3 × 10^5 copies/mL. All patients had varying degrees of intestinal ulcers endoscopically, and the ulcers and pathology were uncharacterized and misdiagnosed mostly as inflammatory bowel disease (IBD). The course of the disease was progressive and later complicated by intestinal bleeding, intestinal perforation, septic shock, and a high rate of emergency surgery. However, the conditions of the patients often did not improve after surgery, and some patients soon died due to reperforation or massive hematochezia. Hormone and antiviral treatment had no obvious effect. There was a significant difference in surgical and nonsurgical survival (p < 0.05). The proportion of patients who died within 6 months was as high as 63.6% (7/11). CAEAE belongs to a group of rare, difficult conditions, has an insidious clinical course, has a high case fatality rate, and may later develop into EBV‐positive lymphoproliferative disorder (EBV‐LPD), which in turn leads to carcinogenesis. Clinicians should raise awareness that in patients with multiple ulcers in the intestine of unknown etiology, attention should be paid to EBV serology, and histology to make the diagnosis as early as possible.